2022
DOI: 10.3390/antiox11061094
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Theobroma cacao L. on the Efficacy and Toxicity of Doxorubicin in Mice Bearing Ehrlich Ascites Carcinoma

Abstract: Background and objective: Doxorubicin is a widely used chemotherapeutic agent that causes oxidative stress leading to cardiotoxicity, hepatotoxicity, and nephrotoxicity. In contrast, Theobroma cacao L. has been recorded as an anticancer agent and found to be protective against multiple chemical-induced organ injuries, including heart, liver, and kidney injuries. The present study investigated the possible role of extracts from T. cacao beans for organ-protective effects in doxorubicin-induced toxicity in mice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 65 publications
(65 reference statements)
1
3
0
Order By: Relevance
“…In the present study, we observed the amelioration of various oxidative stress biomarkers in multiple organs after COE co-treatment with doxorubicin. Moreover, our previous studies also support the efficacy of COE in ameliorating oxidative stress and cancer progression ( Patil et al, 2022b ; 2022a ). Emmanuel et al reported that cocoa leaf polyphenolic-rich extract inhibited xanthine oxidase due to the flavonoids and phenolic acids present in the extract ( Irondi et al, 2017 ).…”
Section: Discussionsupporting
confidence: 66%
“…In the present study, we observed the amelioration of various oxidative stress biomarkers in multiple organs after COE co-treatment with doxorubicin. Moreover, our previous studies also support the efficacy of COE in ameliorating oxidative stress and cancer progression ( Patil et al, 2022b ; 2022a ). Emmanuel et al reported that cocoa leaf polyphenolic-rich extract inhibited xanthine oxidase due to the flavonoids and phenolic acids present in the extract ( Irondi et al, 2017 ).…”
Section: Discussionsupporting
confidence: 66%
“…Mez (= Mespilodaphne sassafras Meisn.) canela-sassafrás, sassafrás essence 105, 108 Root Native c Aromatic root used in therapy (undefined) and essences Antifungal [ 90 ]; anticoagulant [ 91 ] Lecythidaceae Lecythis ollaria L. sapucaia, camari-macaco 85,103 Almonds Exotic Food and medicinal (undefined) Wound healing [ 92 ]; Selenium poisoning (e.g., alopecia) [ 93 , 94 ] Loganiaceae Spigelia anthelmia L. not mentioned 104 Not mentioned Native Poisonous when fresh and vermifuge when dry Anthelmintic † [ 95 , 96 ]; cardiac contraction [ 97 , 98 ]; neuromuscular blockade [ 99 ] Malvaceae Theobroma cacao L. cacaueiro 103 Cacao butter Native Medicinal (undefined) Antioxidant [ 100 , 101 ]; anti-inflammatory [ 102 ]; neuroprotective [ 103 ]; cardioprotective, hepatoprotective and nephroprotective combined with doxorubicin [ 104 ]; antialopecia [ 105 ] Meliaceae Carapa procera DC. (= Carapa guyanensis Oliv.)…”
Section: Resultsmentioning
confidence: 99%
“…However, the groups pretreated with extracts and standards counteracted these anomalies, conceivably a result of the decrease in the inflammatory markers suggestive of reduction in the cardiomyocyte injury in the pretreated groups that was consistent with the outcomes described by other researchers. 4 , 36 The ECG parameters are shown in Figure 5 b–f. In RR, PR, QRS, QT, and QTC interval, a significant decrease ( p < 0.01 (low dose extract group) and p < 0.001 (high dose extract group and standard simvastatin and vit E group)) was seen in contrast to the control DOX group.…”
Section: Resultsmentioning
confidence: 99%